Consenting to Exclude? Empirical Patterns of Democracy and Immigrant Integration Policy - Manatschal, Anita; Bernauer, Julian (My University, 2016)
Studies explaining immigrant integration policies commonly focus on single aspects such as right-populist party politics or the immigration legacy of a country. This neglects the overall character of the democratic system within which policy-making unfolds. Research on empirical patterns of democracy, in turn, suggests that consensus democracies pursue ‘kinder and gentler’ policies and outperform majoritarian democracies in terms of minority representation. The article tests whether this conclusion holds for the specific group of immigrant minorities and analyses the relationship between patterns of democracy and immigrant integration policy using a new dataset on empirical democracies in 30 European and North American countries. Simultaneously estimating the character of democratic systems in terms of power dispersion and its effect on integration policies, the analysis reveals a distinct ‘Janus-faced’ pattern: while proportional power dispersion tends to coincide with more inclusive immigrant integration policies, pronounced veto structures tend to foster exclusion.
Keywords: empirical patterns of democracy; immigrant integration policy; right-populist parties; immigration legacy; Bayesian measurement and outcome models